The Development in Teaching Materials of Introduction to Business Using Business Planning: The Study to the Students at University of Muhammadiyah Sumatera Utara - Jasman Saripuddin S.E., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
One of the objectives of business planning is to provide information to the parties in need that will be used to make comparison, to assess the ability of a company, as well as to be a guide for decision making.